Buku Ilustrasi Parabuangan Khas Daerah Kurai Bukittinggi, Sumatera Barat - Meriza Geovany; Eko Purnomo (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
Parabuangan is a typical dessert from the Kurai region of Bukittinggi, which has strong cultural and customary values in Minangkabau society. However, along with the times, the younger generation, especially Generation Z, is increasingly less familiar with the existence and meaning of this parabuangan. This research aims to design a illustration book as a medium for education and preservation of Kurai's typical parabuangan culture with an attractive and interactive visual communication design approach. The design method used is the Glass Box method which includes the stages of preparation, incubation, lumination, and verification. Data was collected through observation, interviews with traditional leaders, and literature study. The results show that colourful and interactive illustrative designs can increase the younger generation's interest in traditional culinary culture. Expert validation and feasibility testing to the target audience showed that this book is well received and has the potential to be an effective educational media. The implication of this design is the importance of innovation in preserving local culture through a visual approach that suits the characteristics of today's young generation.